The extended drop weight testing approach – What it reveals. (1st October 2020) - Faramarzi, Farhad; Napier-Munn, Tim; Morrison, Robert; Kanchibotla, Sarma S.
Highlights: The new ExDWT was used to measure the breakage potential (A × b) of rock particles. Multidimensional definitions of particle size generate higher (softer) A × b. Diametrally oriented cores give higher A × b values than irregular shaped particles. Ore heterogeneity is the main source of breakage variability measured by the ExDWT. The JKDWT and ExDWT methods give statistically equivalent values of mean A × b. Uncertainty in the mean A × b estimate was up to five times less with the ExDWT. Abstract: The heterogeneous nature of orebodies introduces large uncertainties into all quantitative evaluations, process design and process predictions. Measuring the extent of the variability of ore competence will allow the design process to account for variation in process performance through a quantitative knowledge of its uncertainties related to ore hardness. The conventional JKMRC drop-weight test (JKDWT) establishes the relationship between input energy (Ecs) and product fineness (t10 ) from which the breakage potential parameter A × b can be estimated, by combining the broken progeny of groups of particles. A new method, the Extended Drop Weight Test (ExDWT), has been developed which is applied to individual particles and is therefore capable of capturing breakage heterogeneity at high resolution. This paper explores a number of features of the new method, based on breakage tests on individual particles from several different rock types. The results showed that more accurate descriptions of particle size resulted in higher (softer) A × b values which suggests that the standard method may have been over-estimating rock competence. Regular-shaped cores broken diametrally were found to have higher (softer) A × b values than axially broken cores and irregular shaped particles. These tests also suggested that the true ore intrinsic heterogeneity is the main source of breakage variability measured by the ExDWT. The mean A × b values determined by the ExDWT showed no statistical difference to those determined by the standard JKDWT method, but the standard deviation of the estimate was much lower. The results have demonstrated the potential of the new method for capturing the inherent heterogeneity of individual ore particles. Such information could be used to populate multi-component models of comminution.